14.0k views
3 votes
I need help please help

I need help please help-example-1

1 Answer

3 votes

Answer:

C. (x-2)^2=7

Explanation:

What you have to do first is to get rid of the 3 in the x^2 so you will divide 3 by the whole thing to get x^2-4x=3.

You will then divide -4 by 2 and then square the answer to get 4.

You will then add the 4 into the end of the equation and to the 3 to get x^2-4x+4=7.

You will then make into a perfect square (x-2)^2=7 and that is your answer.

User Rinsad Ahmed
by
6.2k points